2001
DOI: 10.1034/j.1399-3046.2001.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of mycophenolate mofetil and cyclosporin reduction in children with chronic transplant nephropathy

Abstract: Chronic transplant nephropathy (CTN) is the most important cause of kidney graft dysfunction. Studies in adult populations have reported a beneficial effect of non-nephrotoxic mycophenolate mofetil (MMF) on graft function in this setting. However, few studies were reported in children in this setting. We therefore reviewed the charts/medical records of renal transplanted patients < 18 yr of age at a single center who had switched from azathioprine to MMF as a result of progressive loss in graft function, for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
6
19
0
2
Order By: Relevance
“…The main side effect observed with MMF administration was gastrointestinal disturbance, requiring MMF withdrawal in one patient and dose reduction in a further two. This is comparable to findings reported by David-Neto et al [27].…”
Section: Side Effectssupporting
confidence: 94%
See 1 more Smart Citation
“…The main side effect observed with MMF administration was gastrointestinal disturbance, requiring MMF withdrawal in one patient and dose reduction in a further two. This is comparable to findings reported by David-Neto et al [27].…”
Section: Side Effectssupporting
confidence: 94%
“…The findings in our study are supported by the work of David-Neto et al [27], where MMF was substituted for azathioprine together with a concurrent reduction in the CycA dose in 13 paediatric patients, 11 of whom showed evidence of CAN. As in our study, the authors report that the plasma creatinine levels had significantly improved 6 months after the introduction of MMF, this improvement being maintained at a follow up 17.5 months later.…”
Section: Renal Functionsupporting
confidence: 92%
“…Over 1 year, seven of 10 in the former group and six of nine in the latter experienced stabilized or improved graft function; of those receiving SRL, 70% developed transient hyperlipidemia and 40% required erythropoietin to treat anemia. Other studies have demonstrated successful CsA reduction or withdrawal following introduction of MMF in pediatric renal transplant patients with CAN (47) or CsA nephrotoxicity (48). In each case, there were marked improvements in graft function following the introduction of MMF (47,48).…”
Section: Clinical Outcomes Of Newer Regimens In Pediatric Renal Transmentioning
confidence: 97%
“…4 mg/kg body weight/day) for long-term immunosuppression is used without a higher prevalence of CsA nephrotoxicity [35, 36]. Therefore we speculate on a specific suspectibility of CsA nephrotoxicity in a given kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric patient population David-Neto et al [35]documented the safety of CsA reduction from a median dose of 6.69 mg/kg body weight/day to 4.8 mg/kg body weight/day (in four patients even withdrawal of CsA) and the addition of mycophenolate-mofetil, with no observed rejection episode. It is of note that in our patients the median CsA dosage (2.0 mg/kg body weight/day) was already in the lower range (133 ng/ml CsA trough level).…”
Section: Discussionmentioning
confidence: 99%